2008
DOI: 10.1177/0165025408097134
|View full text |Cite
|
Sign up to set email alerts
|

Family correlates of children's social and physical aggression with peers: Negative interparental conflict strategies and parenting styles

Abstract: This investigation examines whether negative interparental conflict strategies (stonewalling, triangulation, verbal aggression, and physical aggression) and parenting styles are related to social and physical aggression with peers for children followed longitudinally from age 9 to 10 (N = 256). Parents reported on negative conflict strategies and parenting styles at the beginning of the study and teachers rated children's social and physical aggression with peers when children were in the 3rd and 4th grades. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 79 publications
(150 reference statements)
2
29
0
1
Order By: Relevance
“…These variations can also be attributed to the inconsistency in the indicators used to examine each one of the parenting styles. Consequently, Underwood, Beron, Gentsch, Galperin, and Risser (2008) indicated that more specific parenting processes need to be used when examining the effects of parents' behavior on children's outcomes. This is true especially with some existing measures that confound the indicators of authoritarian parenting styles by including corporal punishment, while other studies focus only on the demanding aspects of being authoritarian.…”
Section: Parenting Styles and Identitymentioning
confidence: 99%
“…These variations can also be attributed to the inconsistency in the indicators used to examine each one of the parenting styles. Consequently, Underwood, Beron, Gentsch, Galperin, and Risser (2008) indicated that more specific parenting processes need to be used when examining the effects of parents' behavior on children's outcomes. This is true especially with some existing measures that confound the indicators of authoritarian parenting styles by including corporal punishment, while other studies focus only on the demanding aspects of being authoritarian.…”
Section: Parenting Styles and Identitymentioning
confidence: 99%
“…Future studies should include additional variables in predictive models. These include personality variables such as agreeableness (Gleason, Jensen-Campbell, & Richardson, 2004), anxiety and anger (Wittmann, Arce, & Santisteban, 2008); family variables such as parental relationships (Underwood et al, 2008) and parent-child attachment (Michiels, Grietens, Onghena, & Kuppens, 2008); behaviors such as videogaming (Willoughby, Adachi, & Good, 2012); and genetics (Tackett, Waldman, & Lahey, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Nelson and Crick (2002) and Nelson, Hart, Yang, Olsen, and Jin (2006) found parental control (a dimension of authoritarianism) related to girls' social aggression. However, multiple studies have failed to identify such relations (e.g., Underwood, Beron, Gentsch, Galperin, & Risser, 2008). Underwood et al (2008) maintain that measurement error may account for these failures because parenting has been assessed using self-report, which may not be valid.…”
Section: Parentingmentioning
confidence: 99%
See 2 more Smart Citations